Pengembangan Buku Panduan Konseling Kelompok Teknik Role Playing Untuk Meningkatkan Kecerdasan Interpersonal Siswa SMA - Alfia Putri Ligeana Vat; Putu Ari Dharmayanti; Dewi Arum Widhayanti Metra Putri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to develop a group counseling guidebook with role playing techniques to improve interpersonal intelligence of high school students, as well as to test the content validity and test the effectiveness of the developed guidebook. The research and development procedure by used the 4D method (Define, Design, Develop, Disseminate). Tthe validity contents test of the guidebook based on three aspects, namely the usability aspect, the feasibility aspect, and the accuracy aspect. Result of the validity test by experts and practitioners were analyzed using CVI (Content Validity Index) obtained value of 0.77, this stated that the guidebook being developed had a content validity index categorized as very appropriate. To find out the effectiveness of implementation of the guidebook was obtained with through the one group pretest-posttest experimental were analyzed by applying the t-test formula. Result of the effectiveness test get Sig. (2-tailed) of 0.001 which means the application of group counseling guidebooks with role playing techniques is effective to improve interpersonal intelligence of high school students.